REVIEW OF SECONDARY METABOLITES FROM SEVERAL UNCARIA PLANTS IN EAST KALIMANTAN - -, Erwin (Jurusan Kimia FMIPA UNMUL, 2020)
Uncaria is a plant genus that is distributed mainly in tropical and subtropical areas. About 38 Uncaria species grow in the Asia Pacific region. Based on a literature study, it was found that five Uncaria species in the tropical rain forests of East Kalimantan. Several species of Uncaria have long been known and used in traditional medicine such as treating asthma, cancer, diabetes, rheumatism, neurodegenerative diseases, mouth sores, diarrhea and dysentery, sore throat, and gums. The content of secondary metabolites includes flavonoids, polyphenols, terpenoids, alkaloids, iridoids, and coumarin.